“Die Buchwelt zu Gast in Frankfurt”: Understanding the Impact of the Guest of Honour Presentation at Frankfurt Book Fair on the German Literary Marketplace - Norrick-Rühl, Corinna (Mémoires du livre / Studies in Book Culture, 2020)
Since 1976, Frankfurt Book Fair (FBF) management has pinpointed a focus theme for the fair, starting out with a focus on Latin America. From 1988 onwards, FBF has annually invited one country/region to present itself and its authors, literature and culture at the fair as “Guest of Honour.” This paper will discuss the effects of the Guest of Honour presentation, using as its basis a dataset that compares number of fiction translations into German from the source languages of the Guests of Honour. Overall, the contribution will consider the way the Guest of Honour status shapes the literary field in Germany in the year of the presentation and in the years following the presentation. It is also meant as an impulse for further research on the Guest of Honour presentations at FBF.